Eighties People New Lives in the American Imagination - Ferguson, Kevin L.; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
Through an examination of 1980s American cultural texts and media, Kevin L. Ferguson analyzes how new types of individuals were created in order to manage otherwise hidden cultural anxieties during the American 1980s. Exploring a variety of strategies for fashioning self-knowledge in the decade, this book illuminates the hidden lives of surrogate mothers, crack babies, persons with AIDS, yuppies, and brat packers. These seemingly simple stereotypes in fact concealed deeper cultural changes and issues relating to race, class, and gender. Through a range of texts, Eighties People shows how the commonplace reading of the 1980s as a superficial period of little importance disguises the decade's real imperative: a struggle for self-definition outside of the limited set of options given by postmodern theorizing.
Keywords: Sociology; Civilization-History.; United States-History.